The use of free and open source software by Icelandic software developers - Hildur Björns Vernudóttir 1975 (2010)
This thesis presents a study made on the use of Free and Open Source software (FOSS) in software development in Iceland. Structured interviews with 12 practitioners from 12 Icelandic software development companies were conducted. The results show that seven out of twelve companies use a combination of FOSS and proprietary software in development. There are six main reasons practitioners give for using FOSS in their software development. First, it is cheaper; second, it can be implement on any computer without licensing issues; third, it uses open standards; fourth, it is flexible; fifth, it is portable, and sixth and finally it contributes to less vendor lock-in. On the other hand, there are five main reasons practitioners give for not using FOSS for software development. First, the user interface of proprietary software is more appealing than of FOSS; second, it is easier to exchange data outside the company; third, the knowledge is already inside the companies because almost everybody learn to use proprietary software in school, since at least today proprietary software is dominant in the university environment; fourth, there are more functions or features in proprietary software than FOSS, and fifth and lastly, proprietary software has more reliable quality. The results show that more small-sized companies (EU SMEs definition) are using FOSS than micro-sized companies which is very surprising for it was assumed that micro-sized companies (usually start-up companies) had lesser funds and would therefore use more FOSS than larger companies. Þessi ritgerð fjallar um niðurstöður rannsóknar á notkun á frjálsum og opnum hugbúnaði hjá íslenskum hugbúnaðarfyrirtækjum. Það voru tekin viðtöl við 12 aðila frá 12 íslenskum hugbúnaðarfyrirtækjum. Niðurstöðurnar sýna að sjö af tólf fyrirtækjum nota bæði frjálsan og opinn hugbúnað og séreignarhugbúnað við þróun á hugbúnaði. Viðmælendurnir gáfu upp sex megin ástæður fyrir notkun á frjálsum og opnum hugbúnað í hugbúnaðarþróun. Í fyrsta lagi, því hann er ódýrari, í öðru lagi ...